DEVELOPMENT OF MILITARY PRISONERS IN THE PERSPECTIVE OF MILITARY INTEREST - ARIEF FAHMI LUBIS (CV KULTURA DIGITAL MEDIA, 2020)
Guidance for prisoners in Correctional Institutions is inseparable from a dynamic, which aims to provide more provisions for prisoners in returning the TNI's identity as before, namely being able to carry out their duties and responsibilities in the unit so that the Military Correctional Institution (Lemasmil) is the final stage of the system. law enforcement within the Military Courts. The purpose of this study was to determine whether the development of Military Prisoners in Military Correctional Institutions has been going well. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study indicate that the separation of places to undergo punishment for military convicts from civilian convicts is absolutely necessary, because the Penitentiary for civilian prisoners is different in nature and the desired outcome with military convicts.